К вопросу об источниках грамматических знаний славянского языка в среде василиан: Из истории вильнюсского университетского экземпляра грамматики Мелетия Смотрицкого 1619 года - Кажуро, Инна (Acta Polono-Ruthenica, 2021)
There is a copy of Meletius Smotrytsky Grammar, published in 1619 in Yev’ye (Vievis), which is kept in the Library of Vilnius university (the shelf number – Rk 337) nowadays. Despite the fact that the main information about this copy was published in 1908, some of its features were overlooked. The aim of the research is to reveal, by using methods of bibliographical analysis, all the material features of the copy of Smotrytsky Grammar before its release (the structure of the book, types, ornaments) and after it was published (bookbinding, damages and restorations, provenances and annotations). During the research several owners of this copy were identified – three clergymen (priest Grzegorz Sanocki, student of Vilnius Pontifical Seminary Procopius Hucewicz, and Basilian Samuel Nowicki) and several institutions. Procopius Hucewicz and Samuel Nowicki belonged to the Greek Catholic Church of the Polish-Lithuanian Commonwealth. The newly established facts related to the use of Smotrytsky‘s Grammar by monks offer a basis for further research on the reception and impact of Smotrytsky’s scholarly legacy among the Basilians of the Grand Duchy of Lithuania and the Polish-Lithuanian Commonwealth. The findings of the study may be valuable for several historical directions; among those of note are studies of the book culture of the 17th and 18th centuries, as well as the textual scholarship of the liturgical texts of the Greek Catholic Church.